Т. 2 - Бондарев А. А. Александр Александрович; Гутыря С. С. Сергей Семенович; Дьяконов А. А. Александр Анатольевич; Иванов В. П. Владимир Петрович; Ингеманссон А. Р. Александр Рональдович; Исаев А. Н. Альберт Николаевич; Крайнев Д. В. Дмитрий Вадимович; Лебедев А. Р. Алексей Романович; Лесняк С. В. Сергей Васильевич; Морозова А. В. Анна Валентиновна; Песин М. В. Михаил Владимирович; Цимберов Д. М. Дмитрий Михайлович; et al. (2014, 2014)
50-летию Юго-Западного государственного университета посвящается.